STATUS OF COCONUT RESEARCH, DEVELOPMENT AND UTILIZATION IN TANZANIA - E. N. BALINGASA (International Coconut Community, 1989)
Coconut is an important economic crop in the coastal belt of Tanzania and the island. However, production has been dwindling through the years due to various constraints, eg, poor plantation management, lack of improved planting materials, insect pests ‑ notably Oryctes monoceros Oliv, and the coreid bug, Pseuclotheraptus wayi Brown plus a lethaf‑disease presently belie to be caused by mycoplasmalike organisms. To offset further decline of the industry, the National Coconut Development Programme was created by the Ministry of Agriculture and Livestock Development, assisted by the Federal Republic of Germany and the World Bank. Production promotion activities were implemented ‑ conducting selection works on the East African Tall coconut population, establishment of seed gardens to produce high yielding planting materials and supporting extension to disserninate technical information. Simultaneously, researches in agronomy, breeding, pest and disease control were conducted. Lately, farming systems research was added as a new project component. Significant findings on the various research areas are discussed in this paper plus some aspects of utilization, processing and marketing.